2005
DOI: 10.1080/00016480510027493
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of binaural hearing provided through bimodal stimulation via a cochlear implant and a conventional hearing aid: A 6-month comparative study

Abstract: Postoperatively, superior speech recognition ability in quiet and in noise for disyllabic words was achieved using bimodal stimulation in comparison to performance for either monaural aided condition. Mean improvement in speech recognition in the bimodal condition was significant over performance in the CI-alone condition for disyllabic words in quiet at 70 (p=0.006) and 55 dB SPL (p=0.028), for disyllabic words in noise at +10 dB with speech and noise spatially separated with the noise source closest to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 14 publications
6
83
1
8
Order By: Relevance
“…HS is a physical phenomenon, which occurs when speech and noise sources are spatially separated. The intensity of the noise source is reduced at the ear further from the source due to attenuation by the head and shoulders, hence benefiting the contralateral ear with a better signal-to-noise ratio (SNR) for speech perception (e.g., see Morera et al, 2005). SQ relies upon the ability of the central auditory system to compare interaural differences when the speech and noise sources are spatially separated and to selectively target the speech signal for improved intelligibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HS is a physical phenomenon, which occurs when speech and noise sources are spatially separated. The intensity of the noise source is reduced at the ear further from the source due to attenuation by the head and shoulders, hence benefiting the contralateral ear with a better signal-to-noise ratio (SNR) for speech perception (e.g., see Morera et al, 2005). SQ relies upon the ability of the central auditory system to compare interaural differences when the speech and noise sources are spatially separated and to selectively target the speech signal for improved intelligibility.…”
Section: Introductionmentioning
confidence: 99%
“…This was true both when speech and noise were spatially coincident and spatially separated. Morera et al (2005) also evaluated speech perception at a fixed SNR for 12 adults with bimodal devices at 6 months post-implantation. Contrary to the large effect of HS observed in studies with bilateral CIs, Morera et al (2005) reported no evidence of a significant effect of HS for bimodal listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports suggested that listening with a CI and an HA might be better than listening with either device alone [54][55]. These two inputs apparently can be combined successfully and provide beneficial binaural hearing [56][57][58][59][60][61][62][63]. In a small sample, speech recognition in quiet and noise was reported for three subjects who had used a CI and an HA for more than 5 years [64].…”
Section: Speech Recognitionmentioning
confidence: 96%
“…The benefits of cochlear implantation have been well documented and include better speech perception in quiet and noise (e.g., Parkinson et al, 2002;Tyler et al, 1995Tyler et al, , 2002Waltzman et al, 1999) and an improved quality of life (e.g., Maillet et al, 1995;Summerfield et al, 2006;Vermeire et al, 2005). Research also suggests that bilateral device use through two cochlear implants (CI+CI) or a cochlear implant plus hearing aid in opposite ears (CI+HA) provides important auditory cues to both ears, thus allowing for potential binaural hearing advantages (Armstrong et al, 1997;Ching et al, 2001Ching et al, , 2004Ching et al, , 2005Dorman et al, 2004;Dunn et al, 2005;Litovsky et al, 2006;Luntz et al, 2005;Laszig et al, 2004;Morera et al, 2005;Shallop et al, 1992;Tyler et al, 2002Tyler et al, , 2006Tyler et al, , 2007van Hoesel & Tyler, 2003;Waltzman et al 1992). As shown by Zurek (1993), the advantages of hearing with two ears include binaural summation (or combining the intensity or loudness a signal when presented bilaterally versus monaurally), binaural squelch (or combining inputs from the two ears to improve the overall signal-to-noise ratio), and localization (using differences in time, intensity, and spectrum across ears to compare the location of a sound source in space).…”
mentioning
confidence: 99%